Diseño teórico de una planta de producción de biogás a partir de residuos de naranja en la ciudad de Bogotá. (2022)
In the development of this degree work, an alternative for the use of organic waste such as orange peels and bovine excreta is presented, in addition to a possible design of a plant that can be used for the production of biogas. Initially, the concepts and principles of biogas production were researched, including: composition and properties of biogas, characteristics and composition of orange peel and bovine excreta, the process of anaerobic digestion was studied, where throughout the first chapter the different stages that comprise the process are described; hydrolysis, fermentative or acidogenic stage, the acetogenic stage and the methanogenic stage. Finally, in this chapter, a bibliographic review of the digester technologies currently available was carried out, and from this information the digester to be used for the respective plant design was chosen.